A pilot study to improve pain phenotyping in head and neck cancer patients - Ye, Yi; Cardoso, Diovana de Melo; Kayahara, Giseli Mitsuy; Bernabé, Daniel Galera (Frontiers in Pain Research, 2023)
Pain associated with head and neck cancer (HNC) is difficult to manage and reduces quality of life. It has been increasingly recognized that HNC patients exhibit a wide range of pain symptoms. Here we developed an orofacial pain assessment questionnaire and conducted a pilot study to improve pain phenotyping in HNC patients at the diagnosis. The questionnaire captures the following pain characteristics: pain intensity, location, quality, duration, and frequency; the impact of pain on daily activities; changes in smell and food sensitivities. Twenty-five HNC patients completed the questionnaire. 88% patients reported pain at the site of tumor; 36% reported multiple pain sites. All patients with pain reported at least one neuropathic pain (NP) descriptor, 54.5% reported at least two NP descriptors. The most common descriptors were "burning" and "pins and needles". Most patients reported pain to sour or hot/spicy food/drinks, and to food with coarse/hard textures. Patients exhibited impaired oral function, especially chewing, talking, mouth/jaw opening, and eating. Tumor progression has a significant impact on pain. Nodal metastasis is linked to pain at multiple body sites. Patients with advanced tumor staging experience greater pain at the primary tumor site, when exposed to hot or spicy food/drinks or food with hard/coarse texture, or when eating or chewing. We conclude that HNC patients experience a wide range of pain symptoms with altered mechanical, chemical, and temperature sensation. Improved phenotyping and stratification of pain in HNC patients will help address the underlying etiology, which may enable personalized therapeutic approaches in the future.